Assessing professional skills development at a third year level - Briguglio, Carmela; Soontiens, Werner; de la Harpe, B. (Teaching and Learning Forum, 2002)
Employers, professional bodies, instructors and students themselves recognise the need for graduates to leave university with a good understanding of both disciplinary content as well as a range of highly developed professional skills. Many universities have responded to this need by encouraging the development of such skills in their programs of study. Curtin Business School has implemented the Professional Skills Project that aims to integrate the teaching and assessing of professional skills into the units of the Bachelor of Commerce degree program.As part of this initiative, the first author successfully won a grant to implement a project that focussed on supporting students' development of their presentation and written communication skills in his third year management unit. These skills were specifically selected based on the lecturer's previous experiences of teaching the unit which showed that while students in CBS are given opportunities to develop their of professional skills throughout the course, there seemed to be a significant variation in students' skill levels. The variation in skill development was particularly apparent in the assessment of group presentations and written assignments in semester one 2001. Thus, opportunities for students to develop these skills were integrated into the unit and data on students' perceptions of their skill development were obtained by them completing a questionnaire at the beginning and end of the unit.In this paper, we outline how the skills were taught and assessed, present the data on the changes in students' perceptions of their skill levels, and discuss the implications for teaching and assessing presentation and written communication skills in the context of the discipline.